DEIXIS EXPRESSION BY MAGDALENA HOELLER IN TED TALKS CHANNEL - Azzahra, Nayla Nurul Alifa; Salsabila, Irgaida Zahra; Kusumawardhani, Paramita (Linguistics and Literature Journal, 2025)
This study investigates the types and functions of deixis used in the TED Talk “Why Love is Harder in a Second Language (2025)”. The research aims to identify and interpret the deictic expressions based on Levinson’s (1983) classification, which includes five types of deixis: person, spatial, temporal, social, and discourse deixis. Using a descriptive-qualitative method, the researchers analyzed the transcript of the speech and identified sentences containing deictic elements. The results reveal that all five types of deixis are present in the speech with varying frequencies. Person deixis appears most dominantly through the speaker’s use of I, you, and we, which serve to build rapport, establish participant roles, and create an inclusive atmosphere. Spatial deixis is used metaphorically rather than physically to guide the audience through conceptual and emotional spaces within the narrative. Temporal deixis organizes the sequence of events and highlights contrasts between past and present experiences. Social deixis indexes interpersonal relationships and cultural identities, while discourse deixis contributes to textual cohesion by referring to earlier or upcoming parts of the speech. Overall, the findings demonstrate that deixis plays an essential role in shaping meaning, constructing narrative flow, and supporting intercultural communication in speech. This study suggests that further research explore deixis in various digital communication contexts to better understand how reference and orientation operate in contemporary discourse. Keywords: interpretation of deixis, Speech, TED conference, type of deixis